Determining the impact of flow velocities on reactive processes associated with Enterococcus faecalis JH2-2. (4th December 2021) - Chandrasekar, Aparna; Binder, Martin; Liedl, Rudolf; Berendonk, Thomas
Abstract: This study focuses on the impact of infiltration rates on colloidal transport and reactive processes associated with Enterococcus faecalis JH2-2 using water-saturated sediment columns . The infiltration rates influence the physical transport of bacteria by controlling the mean flow velocity. This, in turn, impacts biological processes in pore water owing to the higher or lower residence time of the bacteria in the column. In the present study, continuous injection of E. faecalis (suspended in saline water with varying conditions of dissolved oxygen and nutrient concentrations) into a lab-scale sediment column was performed at flow velocities of 0.02 cm min −1 and 0.078 cm min −1, i.e., at residence times of 1–5 hours. The impact of residence times on reactive processes is significant for field scale setups. A process-based model with a first-order rate coefficient for each biological process was fitted for each obtained condition-specific dataset from the experimental observations (breakthrough curves). The coefficients were converted to a dimensionless form to facilitate the comparison of biological processes. These results indicate that the processes of attachment and growth were flow-dependent. The growth process in the absence of dissolved oxygen was the most dominant process, with a Damkoehler number of approximately 48. HIGHLIGHTS: The influence of flow velocity on bacteria reactive processes like decay and growth was investigated. A combined experimental and modelling approach was employed to determine critical parameters. Dimensionless numbers (Peclet and Damkoehler numbers) were used to compare transport and reactive processes. Growth parameter indicated a dependency on flow velocity in the presence and absence of dissolved oxygen.